2006
DOI: 10.1021/om0607548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bases and Halides on the Amination of Chloroarenes Catalyzed by Pd(PtBu3)2

Abstract: We report a detailed study of the effects of anions on the rates of the amination of aryl halides catalyzed by palladium complexes of the hindered alkylmonophosphine PBu. These reactions occur by turnover-limiting oxidative addition. The extent of the dependence of the rates on the concentration and identity of bases was found to depend on the electronic properties of the haloarenes. The rates of reactions of electron-rich and electron-neutral chloroarenes were independent of the concentration of the bulky alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 49 publications
(95 reference statements)
2
44
0
Order By: Relevance
“…For example, Hartwig has shown that the presence of nucleophilic alkoxides [25] and amines, which form complexes with various intermediates of the catalytic cycle (Scheme 1), leads to alternative catalytic cycle pathways. The nature of the spectator ligand (NHC vs phosphine) additionally complicates the picture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hartwig has shown that the presence of nucleophilic alkoxides [25] and amines, which form complexes with various intermediates of the catalytic cycle (Scheme 1), leads to alternative catalytic cycle pathways. The nature of the spectator ligand (NHC vs phosphine) additionally complicates the picture.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the difference of yields observed upon change of base points to the deprotonation of the Pd-bound amine being the most likely rate-determining step of the process. Compared to the extensive mechanistic and computational studies [25,26] with phosphine ligands conducted by the groups of Buchwald and Hartwig, there is a single DFT computational paper on the Buchwald-Hartwig arylation with carbene ligands. [27] Significantly, this work does not include calculations of the crucial deprotonation of the Pd-bound amine step.…”
Section: Resultsmentioning
confidence: 99%
“…140 Unfortunately, it is not possible to select the base purely on the grounds of the p K a of the free N nucleophile as the p K a is changed significantly by binding to Pd, which typically occurs before deprotonation (Scheme 1). Furthermore, inorganic bases such as Cs 2 CO 3 can act heterogeneously in non-polar solvents where they can behave as much stronger bases than might be predicted from their solution phase p K a value.…”
Section: Key Variablesmentioning
confidence: 99%
“…Further, KOtBu, a relatively strong base, promoted good levels of amination seemingly irrespective of the electronic structure of the aryl halide. [6] This illustrates that amine coordination and deprotonation are not unrelated events. Under mildly basic conditions, strong amine coordination to the metal is necessary to lower the pK a of the metal ammonium salt enough to allow deprotonation to take place.…”
mentioning
confidence: 93%